2015
DOI: 10.1016/j.mod.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Dosage compensation of X-chromosome inactivation center-linked genes in porcine preimplantation embryos: Non-chromosome-wide initiation of X-chromosome inactivation in blastocysts

Abstract: X-chromosome inactivation (XCI) is an epigenetic mechanism that occurs in the eutherian embryo development to equalize the dosage of X-linked genes between males and females. This event is regulated by various factors, and the genes located in the X-chromosome inactivation center (XIC), which is known to be an evolutionary conserved region, are associated with XCI; however, a number of studies regarding this epigenetic event and genomic region are primarily performed in mouse models despite its species-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…This situation was thought to be comparable to other mammalian species, but transcriptional studies in bovine blastocysts refuted this notion, as most X-linked genes were upregulated in female blastocysts compared to their male counterparts (Bermejo-Alvarez et al 2010). This situation was also observed in rabbit and human blastocysts by conducting in situ hybridization (ISH) studies (Okamoto et al 2011), and in pigs, by transcriptional (Park et al 2012) and methylation analyses (Hwang et al 2015), so the mouse model was deemed to be more an exception than a rule for XCI dynamics (Bermejo-Alvarez et al 2012a). Indeed, bovine (Bermejo-Alvarez et al 2010) and rabbit (Okamoto et al 2011) embryos achieve extensive XCI later, around the time of gastrulation, which opens a large window when the upregulation of X-linked genes in female embryos occurs and provides a molecular basis for the appearance of sex-specific phenotypes.…”
Section: Sex Chromosomes Drive Sex Differences In the Absence Of Gonadsmentioning
confidence: 64%
“…This situation was thought to be comparable to other mammalian species, but transcriptional studies in bovine blastocysts refuted this notion, as most X-linked genes were upregulated in female blastocysts compared to their male counterparts (Bermejo-Alvarez et al 2010). This situation was also observed in rabbit and human blastocysts by conducting in situ hybridization (ISH) studies (Okamoto et al 2011), and in pigs, by transcriptional (Park et al 2012) and methylation analyses (Hwang et al 2015), so the mouse model was deemed to be more an exception than a rule for XCI dynamics (Bermejo-Alvarez et al 2012a). Indeed, bovine (Bermejo-Alvarez et al 2010) and rabbit (Okamoto et al 2011) embryos achieve extensive XCI later, around the time of gastrulation, which opens a large window when the upregulation of X-linked genes in female embryos occurs and provides a molecular basis for the appearance of sex-specific phenotypes.…”
Section: Sex Chromosomes Drive Sex Differences In the Absence Of Gonadsmentioning
confidence: 64%
“…40 Diverse mechanisms exist in mammals with respect to the inactivation of XC in females. Generally, accumulation of H3K27me3 results in XC inactivation in females for dosage compensation.…”
Section: Discussionmentioning
confidence: 99%
“…40 In humans, XC dosage compensation has been reported in the preimplantation blastocyst but with conflicting mechanisms. This is consistent with the results of Hwang et al 40 They have reported that the dosage was compensated between the male and female blastocysts. 35 However, the other report concluded that, instead of XC inactivation, dosage compensation during human preimplantation development occurs by downregulation of both X chromsomes in females, a phenomenon named dampening of X expression.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the mechanisms of X-linked gene dosage compensation in female embryos are also evident 3 . The gene dosage compensation with respect to the X chromosomes in female embryos occurs in pre-gastrulation epiblasts in mouse and rabbits 3,8,16 . Notably, human post-implantation and pig pre-gastrulation epiblasts have not been studied 12,16 .…”
mentioning
confidence: 99%